RECONSTRUCTIVE SOCIAL CRITICISM WITHOUT A GENEALOGICAL PROVISO: HONNETH ON METHOD AND THE PATHOLOGIES OF INDIVIDUAL FREEDOM - Segatto, Antonio Ianni [UNESP]; Moura, Matheus Garcia de [UNESP] (Assoc Trentina Sci Umane, 2023)
The article intends to discuss Honneth's methodological model of a reconstructive social criticism with a genealogical proviso. First, we present this proposal by making a brief exposition of what reconstruction and genealogy mean; then, we discuss whether (and how) this model is employed by Honneth after its programmatic formulation based on his reflections on the pathologies of individual freedom. Finally, we intend to point out the following: 1) the combination of the reconstructive and the genealogical paradigms is not pursued by Honneth in subsequent writings; 2) in order to combine both he would have to show that they are reconcilable in respect to the way these paradigms understand the critical capacities of the subjects.
Keywords: Axel Honneth; Reconstruction; Genealogy; Social Pathologies